An interview study of the care manager function—Opening the door to continuity of care for patients with depression in primary care. Issue 3 (28th March 2019) - Udo, Camilla; Svenningsson, Irene; Björkelund, Cecilia; Hange, Dominique; Jerlock, Margareta; Petersson, Eva‐Lisa
Abstract: Aim: To explore experiences among patients with depression of contact with a care manager at a primary care centre. Design: A qualitative explorative study. Methods: During spring and summer 2016, 20 individual face‐to‐face interviews were conducted with patients with experience of care manager contact. The material was analysed using systematic text condensation. Results: The participants described that having contact with a care manager was a support in their recovery process. Care became more available, and the structured continuous contact and the care manager's availability contributed to a trusting relationship. Having someone to share their burden with was a relief. However, it was described as negative when the care manager was perceived as inflexible and not open to issues that the participants felt a need to discuss. For the care manager contact to be successful, there is a need for flexibility and individually tailored contact.